Thyrotoxicosis in a 13‐year‐old girl following pituitary adenectomy for Cushing′s disease. Issue 8 (6th July 2017) - Sigmarsdottir, Arndis Audur; Olafsson, Ingvar Hakon; Kjartansson, Ólafur; Bjarnason, Ragnar
Key Clinical Message: Our objective is to report a case of thyrotoxicosis following pituitary adenectomy for Cushing′s disease, the only pediatric case to our knowledge. No thyroid antibodies were detected, and the thyrotoxicosis was successfully treated for 3 months with no relapse after 5 years of follow‐up. The cause of thyrotoxicosis remains unknown. Abstract : Our objective is to report a case of thyrotoxicosis following pituitary adenectomy for Cushing′s disease, the only pediatric case to our knowledge. No thyroid antibodies were detected, and the thyrotoxicosis was successfully treated for 3 months with no relapse after 5 years of follow‐up. The cause of thyrotoxicosis remains unknown.